2021
DOI: 10.1055/s-0041-1733912
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in Pregnancy: Implication on Platelets and Blood Indices

Abstract: Objective To describe the hematological changes, the platelet indices in particular, in pregnant women with coronavirus disease 2019 (COVID-19) compared to healthy pregnant women. Methods A retrospective case-control study conducted at the Al Yarmouk Teaching Hospital, in Baghdad, Iraq, involving 100 pregnant women, 50 with positive viral DNA for COVID-19 (case group), and 50 with negative results (control group); both groups were subjected to a thorough hematological evaluation. Results Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 22 publications
(36 reference statements)
1
14
0
Order By: Relevance
“…Mental health and stress-related tachycardia were also reported in many SARS-CoV-2 patients [ 23 ]. Moreover, the increase in total WBC noticed in seropositive cases points to an underlying inflammatory process where leukocytosis is triggered as part of the primary immune response to inflammation [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mental health and stress-related tachycardia were also reported in many SARS-CoV-2 patients [ 23 ]. Moreover, the increase in total WBC noticed in seropositive cases points to an underlying inflammatory process where leukocytosis is triggered as part of the primary immune response to inflammation [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…3 % of seropositive cases had dead fetuses, which can be attributed to maternal hypercoagulability state induced by pregnancy, exaggerated by the viral pro-thrombotic effect, added to the fever, and released inflammatory mediators, all of which contribute to thrombosis of placental and umbilical veins, causing fetal death [ 4 , 14 , 25 ]. In a recently published meta-analysis study, the authors studied 1787 seropositive mothers and revealed that only 2.8 % of their neonates tested positive for SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several concerns were raised regarding the viral effect on vulnerable groups, especially pregnant women and newborns. Most of the infections occurred in the third trimester (2). Pregnancy does not seem to enhance the risk of contracting SARS-CoV-2 but increases its severity (3).…”
Section: Introductionmentioning
confidence: 90%
“…The pandemic caused by COVID-19 has cast its shadow on many economic, political, and health aspects. Since the preliminary report of the new coronavirus 2019 due to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in Wuhan, China, 2019, the number of confirmed cases, related mortality, and morbidity have quickly grown (1,2). Several concerns were raised regarding the viral effect on vulnerable groups, especially pregnant women and newborns.…”
Section: Introductionmentioning
confidence: 99%